FAKTOR-FAKTOR DOMINAN YANG BERPENGARUH TERHADAP PENGUASAAN MATERI PEMBELAJARAN MATEMATIKA GURU SMP DI KABUPATEN INDRAMAYU - Senjaya, Aan Juhana (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This study aims to determine the effect of perception toward math, ability of understand of symbols, mastery of basic concepts, and learning motivation toward the mastery of instructional materials of mathematics. The sample of study consisted of 181 Junior High School math teacher. Data were gathered using questionnaires and tests. Data were analyzed using path analysis with Structural Equation Modeling (SEM). The perception toward math as exogenous variable. The ability of understand of symbols, mastery of math basic concepts, and math learning motivation as exogenous or endogenous variable depend on the path diagram. The endogenous variables is the mastery of mathematics instructional  materials. The finding showed that: (a) perception toward math have positive direct effect toward ability of understand of math symbol (?21=0,63); mastery of math basic concepts (?31=50); math learning motivation (?41=0,38); and  mastery of math instructional  materials (?y1=0,21); (b) ability of understand of math symbol  have positive direct effect toward mastery of math basic concepts (?32=0,23); math learning motivation (?42=0,27); and mastery of math instructional  materials (?y2=0,35); (c) mastery of math basic concepts have positive direct effect toward math learning motivation (?43=0,26) and to mastery of  instructional  materials of math  (?y3=0,24); the last (d) math learning motivation have positive direct effect toward mastery of math instructional  materials (?y4=0,24).